Effects of family planning educational intervention packages on oral contraceptive use in Rajchaburi, Thailand. - Gidchawan, Yowvapa (1993)
Oral contraceptive (OC) is a major component of the National Family Planning program (NFPP) of Thailand. The decline in the prevalence of its use during the past caused by the side effects, has brought about a government policy aimed at enhancing continuance of OC. Non-compliance of OC regimen can lead to both indirectly to more frequent side effects and consequently discontinuation and directly to unplanned pregnancy. The purpose of the study is to measure the effectiveness of three Family Planning (FP) educational intervention in enhancing OC compliance and continuance of OC use by determining 1)the effects of FP educational intervention package in terms of changes in FP KAP, compliance to OC regimen, and continuous use, and 2)and interpretive mathematical model for predicting the relationship between client's compliance to OC regimen and continuous use; and the independent variables.